Iglesia y primer franquismo a través del cine (1939-1959) - Comenero Martínez, Ricardo; Moral Roncal, Antonio Manuel (UAH monografías. Humanidades, 2015)
Postwar marked a period of social Catholic restoration for Spain, and at the same time the beginning of a new phase in national cinema based on diverse themes of inquietude. A new period for the relationship between catholicism and cinema had been established.